Explorer: The Lost Islands: Seven Graphic Stories [Book 2], The lost islands - Kibuishi, Kazu, 1978- (New York : Amulet Books, 2013)
Explorer, the exciting graphic anthology series which launched in Spring 2012 with The Mystery Boxes, continues with an incredible roster of comics artists who create amazing new stories around the theme of hidden places in volume two of the series, The Lost Islands.
Rabbit island / Jake Parker -- The mask dance / Chrystin Garland -- Carapace / Jason Caffoe -- Desert island playlist / Dave Roman & Raina Telgemeier ; colors by Braden Lamb -- Loah / Michel Gagne -- Radio adrift / Katie Shanahan & Steven Shanahan ; colors by Eric Kim and Selena Dizazzo -- The fishermen / Kazu Kibuishi ; colors by Jason Caffoe.
Keywords: Explorers -- Comic books, strips, etc; Adventure and adventurers -- Comic books, strips, etc; Comic books, strips, etc -- United States; Explorers -- Fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Comic books, strips, etc; Graphic novels